FEATURES OF PHYSICAL EDUCATION IN GRADES 5-6 OF SECONDARY SCHOOL (Academicia Globe: Inderscience Research, 2022)
The article presents the results of the research conducted to determine the state of health, the formation of motor skills, the development of motor qualities, the formation of interest in physical education and children's sports.We determined the criteria of educational positive moral and volitional qualities, and the preparation of students for passing the norms of the Salomatlik complex.